Chromatin structure can introduce systematic biases in genome-wide analyses of Plasmodium falciparum - Baumgarten, Sebastian; Bryant, Jessica (Open research Europe, 2022)
Background: The maintenance, regulation, and dynamics of heterochromatin in the human malaria parasite, Plasmodium falciparum, has drawn increasing attention due to its regulatory role in mutually exclusive virulence gene expression and the silencing of key developmental regulators. The advent of genome-wide analyses such as chromatin-immunoprecipitation followed by sequencing (ChIP-seq) has been instrumental in understanding chromatin composition; however, even in model organisms, ChIP-seq experiments are susceptible to intrinsic experimental biases arising from underlying chromatin structure. Methods: We performed a control ChIP-seq experiment, re-analyzed previously published ChIP-seq datasets and compared different analysis approaches to characterize biases of genome-wide analyses in P. falciparum . Results: We found that heterochromatic regions in input control samples used for ChIP-seq normalization are systematically underrepresented in regard to sequencing coverage across the P. falciparum genome. This underrepresentation, in combination with a non-specific or inefficient immunoprecipitation, can lead to the identification of false enrichment and peaks across these regions. We observed that such biases can also be seen at background levels in specific and efficient ChIP-seq experiments. We further report on how different read mapping approaches can also skew sequencing coverage within highly similar subtelomeric regions and virulence gene families. To ameliorate these issues, we discuss orthogonal methods that can be used to characterize bona fide chromatin-associated proteins. Conclusions: Our results highlight the impact of chromatin structure on genome-wide analyses in the parasite and the need for caution when characterizing chromatin-associated proteins and features.